2017
DOI: 10.1097/mao.0000000000001574
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Function Change in a Vasopressin-Induced Hydrops Model

Abstract: VP can transiently induce an acute exacerbation of hydrops and asymmetric vestibular dysfunction in guinea pigs. This model could help in studying new treatments for acute hydrops and in explaining the mechanism of bidirectional nystagmus in MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…12 In addition, various animal models of endolymphatic hydrops to date have not been able to reproduce clinical features representative of Ménière's disease, although the latest approach with vasopressin in guinea pigs with surgically induced endolymphatic hydrops has produced more promising results. 13,14 It has even been suggested that endolymphatic hydrops be regarded as an epiphenomenon rather than the underlying aetiology of Ménière's disease. 10 Nevertheless, a meta-analysis of temporal bone studies by Foster and Breeze puts forward a convincing theory that, whilst endolymphatic hydrops probably causes Ménière's disease, it alone is insufficient to cause clinical symptoms and there must be one or more additional cofactors that cause asymptomatic hydrops to become symptomatic Ménière's disease.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, various animal models of endolymphatic hydrops to date have not been able to reproduce clinical features representative of Ménière's disease, although the latest approach with vasopressin in guinea pigs with surgically induced endolymphatic hydrops has produced more promising results. 13,14 It has even been suggested that endolymphatic hydrops be regarded as an epiphenomenon rather than the underlying aetiology of Ménière's disease. 10 Nevertheless, a meta-analysis of temporal bone studies by Foster and Breeze puts forward a convincing theory that, whilst endolymphatic hydrops probably causes Ménière's disease, it alone is insufficient to cause clinical symptoms and there must be one or more additional cofactors that cause asymptomatic hydrops to become symptomatic Ménière's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Egami et al, made clear the role of vasopressin in the endolymph homeostasis and its close contact with inner ear function; administration of desmopressin (a VP type 2 receptor agonist) can exacerbate EH because of acute V2 (vasopressin type 2 receptor)-mediated effects, and, when combined with ES dysfunction, can cause temporary vestibular abnormalities that are similar to the vertiginous attacks in patients with MD [6]. Recently, Kim et al also confirmed that this application of the vasopressin type 2 receptor agonist in experimentally-induced EH produced asymmetric vestibular dysfunction in bidirectional sinusoidal harmonic acceleration test, similar to bidirectional nystagmus in MD [165].…”
Section: Vertiginous or Dizzy Attackmentioning
confidence: 93%
“…Vasopressin type 2 receptors are also found in other sites besides the kidney such as the inner ear and vascular endothelium (35). The use of desmopressin may be associated with a worsening of endolymphatic hydrops in the inner ear through the presence of VR2 in the endolymphatic sac (36)(37)(38)(39). These receptors are also associated with increased levels of clotting factor VIII, von Willebrand factor, and tissue plasminogen activator in endothelial cells (35).…”
Section: Hormonesmentioning
confidence: 99%